Control and Monitoring Automatic Floodgate based on NodeMCU and IOT with Fuzzy Logic Testing - Satriya Ramahdika Utama; Ahmad Firdausi; Galang Persada Hakim (Journal of Robotics and Control (JRC), 2022)
Flood is still a problem that always been a mayor obstacle in several big cities in Indonesia such as DKI Jakarta. If the rainfall so high and river can be accommodate the rainfall, there will be flooding. So that river water doesn’t overflow, it is necessary to make a floodgate in the river flow. One of the previous studies that has been carried out regarding the control and monitoring of water dam gates is researched by Fahruddin. 2014 from the Faculty of Science and Technology, Makassar State Islamic University: Describes the design of a device capable of monitoring the height of water activity in the reservoir and controlling the floodgates automatically according to the height of water activity. The research that the writer is currently carrying out is the design method which consists of a series of sensors, NodeMCU microcontrollers, and Stepper Motors. The workflow of this system is when the water rises or falls, it send a signal to the sensor. And then the signal will be input for the microcontroller which is then processed to turn on the motor, so that it can open or close the floodgates, and send information to the indicator screen and Telegram application. After the experiment is carried out, it can be said that the system can work properly, namely when the ultrasonic sensor experiment, it was found that the sensor has been sent an output signal that was in accordance with the water level in actual condition. Based on testing using the fuzzy method, it was found that opening value at the floodgate obtained during the test had an average accuracy rate of 91% with an error difference of 9%.